The Arc of Return: Afropessimist Temporalities and Relational Justice - Porter, Andrew Stone (Journal of the Society of Christian Ethics, 2025)
Afropessimism is often characterized as nihilistic, and some writers have embraced the label. But Afropessimism also proffers an irreducibly relational theory of justice urging a (re)sensitization to human pain. Reading Afropessimist Cristina Sharpe alongside and against the Enlightenment-optimist Steven Pinker, this paper argues that Afropessimism shares more in common with the Levinasian face summoning to responsibility than with Rawlsian impartiality behind a veil of ignorance. The relational theory of justice, and the fungible temporalities, operative in Afropessimism offer rich resources to Christian ethicists seeking to build effective coalitions. In “staying with the trouble,” Afropessimists insist that a commitment to justice can only be enfleshed in an active and compassionate solidarity with people who are suffering.